2018
DOI: 10.17051/ilkonline.2018.413784
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Öğretmenlerin Okul Öncesi Eğitimin Sorunlarıyla İlgili Görüşleri: Ağrı İli Örneği

Abstract: Bu çalışma öğretmenlerin görüşleri doğrultusunda okul öncesi eğitimin temel sorunlarını belirlemek amacıyla yapılmıştır. Tarama yönteminin kullanıldığı araştırmanın örneklemi Ağrı il merkezindeki okullarda görev yapan 82 okul öncesi öğretmeninden oluşmaktadır. Araştırmacılar tarafından hazırlanan ve 12 açık uçlu soru içeren yazılı görüş formuyla toplanan veriler betimsel analiz yaklaşımı ile analiz edilmiştir. Çalışma sonucunda öğretmenlerin sınıf büyüklüklerinin öğrenci sayısı ve etkinlikler için uygun olmadı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 5 publications
(6 reference statements)
1
3
0
4
Order By: Relevance
“…It is seen that bilingualism has negative reflections on the exercise of the preschool educational programme in terms of subjects such as understanding of activities, following of instructions and completing them. As a result of the research carried out by Ağgül et al (2018), it was revealed, supporting this result of the research, that bilingualism caused problems in implementing the preschool educational programme. Results of the research carried out by Çetin and Yalçın Su (2019) also support this result of the research.…”
Section: Discussionsupporting
confidence: 57%
“…It is seen that bilingualism has negative reflections on the exercise of the preschool educational programme in terms of subjects such as understanding of activities, following of instructions and completing them. As a result of the research carried out by Ağgül et al (2018), it was revealed, supporting this result of the research, that bilingualism caused problems in implementing the preschool educational programme. Results of the research carried out by Çetin and Yalçın Su (2019) also support this result of the research.…”
Section: Discussionsupporting
confidence: 57%
“…Other than these, 2006 research results on the ECTEC were another driving force. The common criticism of international comparative studies (Aras & Sözen, 2012;Aykaç, 2018), comprehensive studies with Turkish samples (Haktanır, Dağlıoğlu, & Güler, 2010), and studies with small samples of ECTEC students (Dereobalı & Ünver, 2009;Özder, Konedralı, & Sabancıgil, 2013;Şahin, Kartal & İmamoğlu, 2013;Uysal, Özen-Altınkaynak, Taşkın, Akman, Dinçer, 2016) and ECE teachers (Ağgül-Yalçın & Yalçın, 2018;Özkut & Kaya, 2012;Öztürk, Zayimoğlu-Öztürk, & Kaya, 2016) was that the 2006 ECTEC was poor on practicum.…”
Section: The Rationale For the 2018 Reformmentioning
confidence: 99%
“…Öğretim elemanlarına göre 2006 programındaki dersler genel olarak uygun fakat yine de bazı dersler 1997 programındaki alternatifinden daha iyi değil ve programın öğretmen adaylarının duyuşsal özelliklerini geliştirme kapasitesi düşüktür (Dereobalı & Ünver, 2009). İmkânları sınırlı (Ağgül-Yalçın & Yalçın, 2018), kültürel farklılıkların fazla olduğu okullarda öğretmenlik (Akdag & Haser, 2010) ve eğitim programını etkin bir şekilde uygulayabilme (Tan-Şişman, 2017) becerilerinin kazandırılmasında da 2006 programının eksiklikleri bulunmaktadır.…”
Section: Türkiye'de Oöö Yetiştirmede Kilometre Taşlarıunclassified
“…İnsanlar çocuklarının daha nitelikli ve geleceğe dönük eğitimler almasını beklemektedirler. Bu nedenle eğitimlerin gerçekleştirildiği kurumların fiziksel yapıları, sahip oldukları olanaklar, sınıflarda bulundurdukları çocuk sayıları, çalıştırdıkları öğretmen nitelikleri, çocuklara kazandırılması düşünülen davranış ve beceriler, ailelerle etkileşim biçimleri vb birçok faktörün öne çıkmaya başladığı hissedilmektedir (Ağgül Yalçın ve Yalçın, 2018). Yapılan araştırmalarda çocuklardaki gelişimin istenilen düzeyde olması ve çocuğun okul öncesi dönemde verilen eğitimden olumlu etkilenerek geleceğini doğru şekillendirebilmesi için bazı kriterlerin önemi vurgulanmıştır (Can ve Kılıç, 2019;Karademir ve Ören, 2020).…”
Section: Introductionunclassified
“…All parents wish their children to receive high quality and future-oriented education. Therefore, the physical facilities of schools, class size, teachers' competence, targeted behaviors and skills, and interaction with parents are becoming more and more critical (Ağgül Yalçın and Yalçın, 2018). Some criteria are of significant importance for the quality of preschool education and its positive impact on children's development (Can and Kılıç, 2019;Karademir and Ören, 2020).…”
Section: Introductionmentioning
confidence: 99%